PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH (STUDI PADA BANK SAMPAH KOTA SURABAYA) - Bella Isnainia Rahmanita Fauzia; Deasy Arieffiani (Faculty of Social and Political Science, 2020)
This This study aims to analyze and describe community participation in Managing Waste Bank in Jambangan District in Surabaya. It also investigates the supporting and inhibiting factors in Managing Waste Bank. The study uses qualitative descriptive method. The results indicate that 1) participation in Decision Making is done through the decision and discussion between waste bank administrators, customers, and neighborhood association, and citizen association, 2) participation in Executing is done by non-governmental organization. The study has an agreement, such as 3) Participation in Taking Benefits that can be seen from quantity and quality aspects according to the number of customers targeted and the advantages, 4) There hasn’t been any evaluation for this program but few evaluations are made. The results show 3R Principles, namely 1) reducing principle has been done according to rules made by Minister of the Environment and Center of Waste Bank in Surabaya, 2) reusing principle has resulted in socializations, 3) recycling principle has resulted in specific parts and to recycle through environment ambassador. Supporting factor in the waste bank in Jambangan District has a grant from CSR (Coorporate Social Responsibility) of PT. PLN East Java. Whereas, the inhibiting factor is still found by residents who do not want to sort out garbage.